Synthesis and Characterization of Bentonite Nanocomposites from Egyptian Bentonitic Clay - Ismaeel, Sameh Hamed; Mabrouk, Mohamed Sayed; Ali, Ali Abd-Almotalib; Abn Elwalead, Khaled (International Journal of Nanotechnology and Allied Sciences, 2017)
The aim of this paper was synthesis of bentonite nano-composites from bentonitic clay. Calcium bentonitic clay obtained from El Barqan area northern Egypt was activated by Na2CO3 and purified. Both raw and purified bentonitic clay were characterized by XRD, XRF, SEM, TGA DTA and TM in addition to the study of the mineralogical composition of non-clay mineral under polarizing microscope. Physico-chemical and geotechnical properties such as Cation Exchange Capacity (CEC), Specific Surface Area (SSA), free swelling, Atterberge limits, GSD, OMC and MC were determined. Purification of raw Egyptian bentonitic clay was used for preparation of bentonitic clay nanocomposites as its high content of montmorillonite. Purification was done by four steps; eliminate the impurity levels of non-clay minerals, eliminate the impurity levels of Fe, eliminate the impurity levels of AL and concentrate montmorillonite in the sample using centrifuge. The grain size analysis, SEM and XRD of purified bentonitic clay showed the average grain size 200- 300 nm with one dimension less than 100 nm and the content of montmorillonite become 95%.